Relapses in Multiple Sclerosis: Definition, Pathophysiology, Features, Imitators, and Treatment - Serhan Sevim (Türk Nöroloji Dergisi, 2016)
Relapse in multiple sclerosis (MS) is defined as a neurologic deficit associated with an acute inflammatory demyelinating event that lasts at least 24 hours in the absence of fever and infection. Myelinoclasis and axonal transection occur in relapses. Diagnosis, prognosis, treatment, and many other features of the disease are directly related to the relapses. MS starts as the relapsing-remitting (RRMS) form in 85% of patients. A large number of relapses in the first years, polysymptomatic relapses, and pyramidal system, brain stem, and spinal cord involvement are signs of a poor outcome. The average frequency of relapses is approximately one per year during the first years of RRMS. The frequency of relapses increases during systemic infections, psychological stress, and in the postpartum first 3 months. Seventy-five percent of relapses are monosymptomatic. Pseudo-relapses and paroxysmal symptoms are distinguished from relapses by their sudden onset, sudden termination, and shorter duration. Contrast enhancement is valuable in imaging, but undetectable in most relapses. The regression in the first few weeks of relapses is explained by reduction of the edema, and by remyelination in the following months. Relapses and their features are also among the main determinants of treatment. High-dose methylprednisolone and early treatment with adrenocorticotropic hormone reduce post-relapse disability and shorten the duration of relapses. Plasmapheresis is a good option for patients who do not respond to steroid treatment. Identification of relapses by patients and physicians, distinguishing them from imitators, proper evaluation, treatment when necessary, and monitoring the results are of great importance for patients with MS. The educational levels of patients and physicians regarding these parameters should be increased. Well-designed studies that evaluate the long-term effect of relapse treatment on disability are needed.